ANALISIS RASIO SOLVABILITAS PADA PT BANK SULUT - Christie Natalia kalesaran; Frendy Pelleng; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2014)
: To cover the shortage of funds, the company will need to obtain funds from its own capital and of leadership. When combining these two sources of funds is called the ratio of borrowed funds or solvency ratio or leverage ratio, which recognizes the extent of the company's assets is financed by debt. The solvency ratio is a tool to measure the wealth assessment company. For this study entitled: Solvency Ratio Analysis in PT Bank of North Sulawesi. Analysis solvency ratio is the ratio used to measure the extent to which the company's assets financed with debt, so that the company can measure the ability to pay all of its liabilities, both short and long term. This study used a descriptive method and analyze the company's financial statements, in particular the analysis the solvency of the PT Bank of North Sulawesi. To determine the extent of the bank's ability to seek funding, to finance their activities and the ability of some element of equity to assets in terms of efficiency. The results show that financial performance under conditions of solvability is the source of funds and property companies, total assets and total liabilities of the company is likely to increase from year to year. Primary level ratio showed a trend increase from year to year; Risk Assets Ratio levels tended to increase from year to year; Capital Ratio experienced a rising trend from year to year, except in 2012 due to declining reserves or losses on earning assets. So the Capital Adequacy Ratio (CAR) also showed rising trend. In conclusion, the level of Primary Ratio, Risk Assets Ratio, Capital Ratio and Capital Adequacy Ratio (CAR) shows the trend of the increase; PT Bank of North Sulawesi can be said as a solvent company, the level of capital adequacy or CAR can be met from 2010 to 2013. As a suggestion, the company's ability to raise or provide funds rely more improved, can satisfy funding for operational activities, in order to increase the level of CAR PT Bank of North Sulawesi remains solvable. Key Word : (Analysis, Solvency Ratio)